Evolution of Public Cooperation in a Risky Society with Heterogeneous Assets - Liu, Linjie; Chen, Xiaojie (Frontiers in Physics, 2018)
The phenomenon of asset heterogeneity is widespread in human society. However, it is unclear what roles heterogeneous assets play in the evolution of cooperation of the collective-risk society. In this paper, we thus introduce asset heterogeneity into a threshold public goods game with collective-risk, and we divide the population into the rich and the poor according to individual assets. We show that asset heterogeneity hinders public cooperation no matter whether the temptation to defect is high or low. We find that cooperation collapses in the conditions of low risk, the high gap between the rich and the poor, and high threshold. Besides, the increment of individual assets can significantly enhance the level of public cooperation even the conditions for the evolution of cooperation are strongly harsh. Our work is instructive to a better understanding of the emergence of cooperation in the risky society with heterogeneous assets.